The Assessment on Health Status and Health Behavior among Aging Workers in Southern Thailand - บัวยอม ปัจฉิมา; จุทอง หทัยทิพย์; ธรรมปาโล สุวิช; วิวัฒน์ ลิเลียน; แก้วปาน วันเพ็ญ (Disease Control Journal, 2010)
The objective of this study was to determine health status, health risk and health promoting behavior among aging workers (45-60 years) in southern of Thailand. Subjects (n=314) were recruited from factories in Songkhla and Suratthani by multi-stage random sampling technique. Questionnaire and focus group discussion were performed for collecting data. Results showed that 64.9 % of aging workers perceived their health status at good level. Personal illnesses were reported at 43.2 %. Only 43.0% had history of annual health checkup examination. About 62.6% of subjects had hyperlipidemia, while 27.3 % were at risk of Diabetes mellitus. Aging workers had abnormal hearing ability and poor visual function at 20.7 and 68.1% respectively. For menopausal symptoms, 63.2% of female workers had estrogen deficiency and 30.4 % of male workers had testosterone deficiency. The aging group had risk behaviors such as regular smoking, alcohol drinking etc. at less than 10%. Most of aging workers had health promotion knowledge at good level (83.4%) and health promotion attitude at moderate level (89.0%). Most of the factories had health promotion policy (91.5%). The participation in health promotion activity was moderately convenient (51.9%) while support from family member was at high level (59.1 %). Aging workers had overall health promoting behaviors at good level (62.3 %). Predisposing factors (knowledge and attitude in health promotion), enabling factors (policy implementation, participation convenience) and reinforcing factors (support from personnel in work place and family members) as well as perceived health status were significantly related to health promoting behaviors (p<0.05). These factors should be considered to improve the health status and health behaviors of aging workers in the further.